Total phenolic and flavonoid compound of crude and purified extract of green tea leaves (Camellia sinensis) from Makassar-Indonesia - Muammar Fawwaz; A. Muflihunna; Mamat Pratama; Rahmawati Rahmawati; Rais Razak; Muzakkir Baits (Jurnal Fitofarmaka Indonesia, 2022)
Polyphenols are a class of chemical compounds most commonly found in plants, these compounds have many health benefits associated with the character it has. The antioxidant activity of natural materials connected by polyphenol content, which can counteract free radicals. Objective: This study aims to determine the levels of total phenolic and flavonoid in crude extracts and purified extracts of the green tea leaves (Camellia sinensis). Methods: Determination of total phenolic content was using standard gallic acid by the Folin-Ciocalteau method. Total flavonoid assay using standard reference of quercetin by Chang method. Instrument used to measure the absorbance of the reaction is a UV-Visible spectrophotometer. Results: The results obtained after the measurement indicates that the sample of crude extract and purified extract of tea leaves containing total phenolic levels 40.5 and 43.9 mgGAE/g, respectively, while the levels of total flavonoids contained respectively by 2.77 and 3.14 mgQE/g. From the results obtained it can be concluded that the green tea leaves have a total phenolic content is greater than the total flavonoid content, thus it has great potential as an antioxidant